IMPACT OF STRESS ON FRONT-LINE / BUSINESS MANAGEMENT EXECUTIVES AND IT'S SOLUTION (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
In today's competitive environment, succumbing to stressful situations is cause of worries. Business environment is uncertain and turbulent and the race to reach the top has increased. The reasons for stress may be attributed to work pressure, peer pressures, family demands, lifestyles etc. Sometimes these stressors are beyond one's control and one may fall prey to number of problems indulge in alcoholic pleasures which have ruined lives. On the other hand there is no room for non performers which may result in loss of job and search for another. These pressures are there to stay closing one's eye is no solution. However it would be wrong to interpret that stress is an unwanted element of one's life .Creation of healthy and non stressful environment has become a key focus for organizations1 The rich Hindu literature has since years contained methods and techniques that will help mankind to face the pressures and maintain a healthy mind, body and soul. This research papers deals in managing stress by understanding some aspects of Vedic literature.